Studi komparatif penguasaan kompetensi pedagogik guru kelas sekolah dasar antara guru alih fungsi dari guru TK, guru alih fungsi dari guru mata pelajaran dan guru sekolah dasar di Kabupaten Kulon Progo - Sumanti Sumanti (Universitas Sarjanawiyata Tamansiswa, 2015)
This study aims to determine: the difference between the teachersâ€™ pedagogical competence of teachers over the function of the kindergarten, the teacher over the function of the subject teacher and elementary school classroom teachers. This research was conducted in Kulon Progo academic year 2013. Kind of research is a quantitative survey method. The study population consisted of some 305 and samples were taken as many as 266. with t-test analysis with ANOVA one lane and proceed with further testing. Processing data by using SPSS 16.0. Descriptive shows the average pedagogical competence. Test of homogeneity of variance shows the same variant group. Anova table shows the significance level group equations pedagogical competence of teachers. Further trials show the degree of difference, where different groups and which group is better. TheÂ p-value for the degree of significance is 0.05. The results of this study indicate that there is a difference pedagogical competence mastery of elementary school teacher better than over the function of the kindergarten teachers and teachers over the function of the subject teacher.